Ideological Contention or a Pragmatic Power Rivalry? A Deductive Approach to Understanding the Rivalry Between Saudi Arabia and Iran - Doueidar, Taha (Université d'Ottawa | University of Ottawa, 2021)
There are not many problems in the Middle East getting more attention than the rivalry between the Kingdom of Saudi Arabia and the Islamic Republic of Iran. Their competition for dominance has permeated throughout the region, making it a critical aspect in almost all major conflicts. The emphasis on religion in political discourse and domestic media implies that ideology is a driving factor of contention. Many journalists and academics have taken this as evidence of an "Islamic Cold War" in the region, as the Cold War was fundamentally an ideological conflict. This paper tests this common hypothesis by drawing out observable indicators from the Cold War and using them to analyze the case of Saudi Arabia and Iran. I argue that ideology is not a driver in the conflict between Saudi Arabia and Iran. They are involved in a classic geopolitical rivalry based primarily on territorial disputes, regional security, and economic issues. My argument is structured around three observable differences; firstly, the Americans and Russians did not have a history of conflict. It is unique to the Cold War because Arabs and Persians have been fighting since antiquity, well before the emergence of Islam. Secondly, American liberalism and Soviet communism were inherently conflicting ideologies that advocated contradictory systems of governance. This is a feature that Wahhabism and Khomeinism do not share. Lastly, the US and Soviet Union had ideologically consistent foreign policies. In the case of Saudi Arabia and Iran, we observe pragmatic foreign policymaking and continuous ideological concessions to progress their geopolitical agenda. These three characteristics of the Saudi-Irani rivalry indicate that we are observing less of an ideological conflict and more of a classic geopolitical rivalry. Key Words: International Conflict; Middle Eastern Affairs; Islamic Cold War; Geopolitics; Foreign Policy; Ideology